Concrete Expressions Brutalism and the Government Buildings Precinct, Adelaide - O'Sullivan, Kevin (Architecture Museum Monograph Series, 2013)
This monograph focusses on a cohesive group of four government buildings constructed in Adelaide during the 1970s. Designed by different architects, the buildings all feature monolithic, austere forms and broadly similar external concrete finishes, and are often described by casual observers as being Brutalist in style. But are any or all of them truly Brutalist?